Desentralisasi Fiskal Dan Tingkat Kemandirian Daerah Kabupaten/Kota di Provinsi Jawa Barat Tahun 2015-2019 - Hardiana, R. Dian; Tanuatmodjo, Heraeni; Kurniati, Fitrina (Universitas Pendidikan Indonesia, 2020)
This study aims to determine the performance of decentralization through Regional Sufficiency in regency/cities in West Java in 2015-2019. Fiscal decentralization gives local governments the authority to manage their own finances within the framework of legislative regulation. The research method used is descriptive, with the object of regency/city research in West Java Province in 2015-2019, the data used were sourced from secondary data released by BPS. The results of the study show that the performance of the implementation of fiscal decentralization indicated by the degree of fiscal autonomy, the ratio of dependency and the ratio of independence is still quite low, although there is an increase in the category of each indicator towards a better direction. Suggestions from the results of the study are that local governments need to increase the capacity of fiscal decentralization through increasing sources of new PAD revenue through innovations such as the development of BUMD, optimization of tax collection and local user fees through intensification and extensification.